Mucho y muy buen vino. Producción vitivinícola en la zona norte de Santiago (siglos XVI -XVIII) - Ruiz Rodríguez, Carlos (Revista de Historia Social y de las Mentalidades, 2025)
Shortly after the Spaniard conquest, in the norther n part of Santiago (places like: La Chimba, Renca, El Salto y Quilicura), started to pr oduce “a great deal and very good quality of wine”. The origin and specifications of the vineyard production during the colonial period is stated here. It is recomposed h ere a descriptive frame about colonial vineyard in that area along with analyzing the econ omical aspects: the evolution of the productive infrastructure, the kinds of soils dedic ated to the wine production, the prices of the soils and plants of grapevines, the use of labo r force (whether they are with salary, slavish or servile). It also includes the impact t he colonial regime and the use of alcohol had in the indigenous population.